One woman's Army : a Black officer remembers the WAC - Earley, Charity Adams, 1918-2002 (Texas A & M University military history series, 1996)
When America entered World War II, the surge of patriotism was not confined to men. Congress authorized the organization of the Women's Army Auxiliary Corps (later renamed Women's Army Corps) in 1942, and hundreds of women were able to join in the war effort. Charity Edna Adams became the first black woman commissioned as an officer. Black members of the WAC had to fight the prejudices not only of males who did not want women in their "man's army," but also of those who could not accept blacks in positions of authority or responsibility, even in the segregated military. With unblinking candor, Charity Adams Earley tells of her struggles and successes as the WAC's first black officer and as commanding officer of the only organization of black women to serve overseas during World War II. The 6888th Central Postal Directory Battalion broke all records for redirecting military mail as she commanded the group through its moves from England to France and stood up to the racist slurs of the general under whose command the battalion operated. The Six Triple Eight stood up for its commanding officer, supporting her boycott of segregated living quarters and recreational facilities. This book is a tribute to those courageous women who paved the way for patriots, regardless of color or gender, to serve their country.